Women's social eating environment and its associations with dietary behavior and weight management. (1st March 2017) - Mötteli, Sonja; Siegrist, Michael; Keller, Carmen
Abstract: As an unhealthy social eating environment is considered a risk factor for obesity, this study aimed to examine women's regular eating networks and the extent to which diet-related variables were associated with those of their regular eating companions. In Study Part I ( N = 579), an egocentric network approach was used to investigate women's perceptions of their eating networks. In Study Part II ( N = 262), the participants' most important eating companions responded to a similar survey, and the corresponding answers were matched. The results showed that women shared their meals most frequently with spouses and other family members. Women who dined more often with healthy eaters reported on average a higher diet quality and a lower body mass index (BMI), which were also significant after controlling for individual factors. Study Part II expanded these results by showing that different diet-related factors such as diet quality, eating styles and BMI were correlated between women and their most important eating companions ( r = 0.16–0.30, p < 0.05). Moreover, an actor–partner interdependence model revealed that a higher diet quality of the eating companions was associated with a lower BMI in women, controlled for their own eating behavior ( b = −0.45, p < 0.05). This study showed similarities and interdependence between women's dietary behavior and body weight and those of their regular eating companions. This might indicate that regular eating networks have a shared understanding of what constitutes a normal diet, which might be an important factor to consider in the promotion of healthy eating.